Turkey's Changing Stance on Immigration: An Examination of Foreign Policy Adjustments - Pertiwi, Delfira Irgahayu; Sinulingga, Anita Afriani; Jamilah, Maryam (As- Sakinah Law Firm & Society of Visual Informatics, 2023)
Turkey was a closed country to immigrants. However, in 2013, Turkey modified its foreign policy to become an open country for immigration under the Law on Foreigners and International Protection. Even in 2019, Turkey is the country that receives the most refugees. The purpose of this research is to examine the impact of Turkish foreign policy changes on immigration. To analyze it, this study employs Blavoukos and Bourantonis' Foreign Policy Change Concept. This study uses a qualitative approach with an explanatory design. The data analysis technique used in this study begins with data reduction, followed by data presentation, findings, and verification. This study discovered that Turkish foreign policy changed as a result of Turkey's desire to join the European Union, the encouragement of President Abdullah Gul and Prime Minister Erdogan, and the shift in Turkish political culture to Neo-Ottomanism.